The Impact of Helicobacter pylori Infection on the Gastric Microbiota of the Rhesus Macaque - Martin, Miriam E. (Public Library of Science, 2013)
Helicobacter pylori colonization is highly prevalent among humans and causes significant gastric disease in a subset of those infected. When present, this bacterium dominates the gastric microbiota of humans and induces antimicrobial responses in the host. Since the microbial context of H. pylori colonization influences the disease outcome in a mouse model, we sought to assess the impact of H. pylori challenge upon the pre-existing gastric microbial community members in the rhesus macaque model. Deep sequencing of the bacterial 16S rRNA gene identified a community profile of 221 phylotypes that was distinct from that of the rhesus macaque distal gut and mouth, although there were taxa in common. High proportions of both H. pylori and H. suis were observed in the post-challenge libraries, but at a given time, only one Helicobacter species was dominant. However, the relative abundance of non-Helicobacter taxa was not significantly different before and after challenge with H. pylori. These results suggest that while different gastric species may show competitive exclusion in the gastric niche, the rhesus gastric microbial community is largely stable despite immune and physiological changes due to H. pylori infection.